If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13 = 10x + -7 Reorder the terms: 13 + 5x = 10x + -7 Reorder the terms: 13 + 5x = -7 + 10x Solving 13 + 5x = -7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 13 + 5x + -10x = -7 + 10x + -10x Combine like terms: 5x + -10x = -5x 13 + -5x = -7 + 10x + -10x Combine like terms: 10x + -10x = 0 13 + -5x = -7 + 0 13 + -5x = -7 Add '-13' to each side of the equation. 13 + -13 + -5x = -7 + -13 Combine like terms: 13 + -13 = 0 0 + -5x = -7 + -13 -5x = -7 + -13 Combine like terms: -7 + -13 = -20 -5x = -20 Divide each side by '-5'. x = 4 Simplifying x = 4
| 1.4m-0.6(m-2)=2 | | (4/5)/12 | | 2-3x=4x-75 | | 1800-60x+1200-45x=c | | 7x+5=-19 | | x(3x)= | | x/3+x=4 | | 300-2p=100+5p | | x-6=-1+3 | | A=1/22015 | | 12(4/5) | | 9-12/5 | | 30+8v+4v-19=20v+16-8v-5 | | 8/(2/3) | | 3x^3-12= | | -4x-1-4x=-33 | | W-15=l | | 6/(3/8) | | 1/6(2x-112)=5x | | 91(-7)-5=35/7+3 | | 8y-7=7y | | (2p+3)-1-3=-4 | | 3--2t=19 | | 6=2r-6+2r | | (3/8)/6 | | 5=15-5/6(5y+8) | | 1/5(2x-112)=5x | | 3+ax=15-bx | | x(3x-4)= | | 35/7+3 | | 3y+120= | | 38/(2/9) |